TERITORI RUANG KOMUNAL BERBASIS WAKAF DI PERMUKIMAN KOTA (STUDI KASUS KAMPUNG KAUMAN SEMARANG) - Agus Rochani; Ardiana Yuli Puspitasari (Jurnal Ilmiah Arsitektur, 2022)
Urban regions nowadays are constrained by a scarcity of land for the construction of community space. The waqf of land is one of the charitable endeavours that has been long-established in the neighbourhood. Because the waqf serves as the primary gathering place for the community that manages it, the Muslim community's act of prayer directly influences the spatial organisation of the city. Waqf is practised by almost all Muslim communities worldwide. Waqf has a significant role in defining the city's community spaces, including as places of worship, places of learning, places of health, economies, businesses, and environmental infrastructure. Seventy percent of urban villages, like Semarang City, hold waqf land. The goal of this study is to provide a description of the area of community space that develops from land waqf in urban communities. Kampung Kauman Semarang was chosen for the study because it is a crowded community representative of urban centres. To comprehend territorial traits that are specifically generated in the midst of people's lives, the research technique employs a holistic single case study methodology. This research contributes to our understanding of how waqf territoriality develops through communal defence and the long-term creation of benefits in a variety of dimensions, reflecting the qualities of sustainable space. Keywords: Territory, Communal space, Land waqf, Urban settlement, Kauman Village